Factors Influencing Fraudulent Financial Reporting: Evidence from State-Owned Enterprises Listed on the Indonesia Stock Exchange - Denny Putri; Santi Octaviani (West Science Accounting and Finance, 2026)
This study investigates the determinants of fraudulent financial reporting in Indonesian state-owned enterprises listed on the Indonesia Stock Exchange during 2020–2024 using the fraud pentagon perspective. The study examines financial target, ineffective monitoring, rationalization, capability, and arrogance as independent variables, while fraudulent financial reporting risk is measured using the F-score model. From 24 listed firms, purposive sampling generated 21 companies with 89 final observations after outlier removal. Multiple linear regression results show that financial target has a positive and significant effect on fraudulent financial reporting. Ineffective monitoring and CEO arrogance also significantly influence fraudulent financial reporting, although both show negative coefficients in this sample. Meanwhile, auditor change and director change do not significantly affect fraudulent financial reporting. The model explains 39.1% of the variation in the F-score and is statistically significant. These findings suggest that fraud risk assessment in state-owned enterprises should emphasize profitability pressure, the quality of board oversight, and managerial communication signals rather than relying solely on governance structure, auditor rotation, or director turnover.